Glycosylation as an intricate post-translational modification process takes part in glycoproteins related immunity - Meng Tian; Xiaoyu Li; Liuchunyang Yu; JinXiu Qian; XiuYun Bai; Jue Yang; RongJun Deng; Cheng Lu; Hongyan Zhao; Yuanyan Liu (Cell Communication and Signaling)
Abstract Protein glycosylation, the most ubiquitous and diverse type of post-translational modification in eukaryotic cells, proteins are input into endoplasmic reticulum and Golgi apparatus for sorting and modification with intricate quality control, are then output for diverse functional glycoproteins that are utilized by cells to precisely regulate various biological processes. In order to maintain the precise spatial structure of glycoprotein, misfolded and unfolded glycoproteins are recognized, segregated and degraded to ensure the fidelity of protein folding and maturation. This review enumerates the role of five immune-related glycoproteins and reveals the relevance of glycosylation to their antigen presentation, immune effector function, immune recognition, receptor binding and activation, and cell adhesion and migration. With the knowledgement of glycoproteins in immune responses and etiologies, we propose several relevant therapeutic strategies on targeting glycosylation process for immunotherapy.